SISTEM PERENCANAAN PEMBANGUNAN DAERAH DI ERA OTONOMI - Evi Oktarina (Justici, 2022)
The growing attention to regional autonomy is not only associated with the failure of centralized planning and the popularity of growth with equality strategies, but also the awareness that development is a complex and uncertain process that cannot be controlled and planned easily from the center. There are six stages in the regional economic development planning process, including (1) data collection and analysis, (2) selection of regional development strategies, (3) selection of development projects, (4) preparation of action plans, (5) determination of project details, and (6) preparation of overall planning and implementation. In the implementation of regional planning, it turns out that many problems arise, including: Propenas (RPJMN) and Propeda (RPJMD) are not sustainable plans because they are only prepared every five years, it is still unclear how and when top-down and bottom-up planning are integrated, there is a large gap in calculating financial capacity, and the planning focuses too much on the development project budget rather than on the overall budget.